Evaluating Credit Cooperative Performance Through PEARLS Standards: Implications for Financial Management (2021–2023) - Henny A. Manafe; Yolinda Yanti Sonbay; Paaskalis Seran (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The increasing role of credit cooperatives in supporting community-based financial inclusion requires continuous performance evaluation to ensure sustainability and competitiveness. Utilizing PEARLS performance standards, this study aims to comparatively analyze the performance of the Adiguna and Sami Jaya Credit Cooperatives for the years 2021 – 2023, and to identify factors that differentiate the performance levels of the two credit cooperatives. This study employs a descriptive quantitative research method by analyzing financial ratio data based on the PEARLS framework. The results show that in terms of protection, financial structure, and growth prospects, the Sami Jaya credit cooperative is found to have better performance compared to Adiguna. Meanwhile, regarding asset quality, return, costs, and liquidity, the two cooperatives are about at the same level in their performances. However, the Sami Jaya credit cooperative has slightly better performance than Adiguna. The average growth of Sami Jaya cooperatives was faster and more efficient. Both cooperatives need to improve their performances, specifically, the Adiguna credit cooperative needs to improve its protection ratio, financial structure, and the rate of return value.